PRAGMATIC APPROACH TOWARDS MENSTRUAL PRACTICES: A CONTEMPORARY, CULTURAL, AND AYURVEDA SCIENCE REVIEW (AYUSHDHARA, 2021)
Menstruation is a biological, cultural as well as now a political phenomenon. In culture and traditions across the globe menstruation is surrounded by secrecy, shame, embarrassment, fear, humiliation, silence, and stigma. Apart from these variables, several studies on menstrual practices also include other variables like bothersome, prohibitions, community, presumptions and seclusion. It is easy in today’s world to forget that menstruation is all about reproductive health. The practice of menstrual taboos in adolescent girls with its implications on hygiene are widely being studied and published. Ayurveda marks menstruating female as ‘Rajaswala’ and instructs to follow certain disciplined life style in terms of diet and routine activities while menstruating. Apart from culture and contemporary science, Ayurveda science believes observance of Rajaswala paricharya must for reproductive health and for procurement of healthy offspring. Present article is a review of various research works on menstrual practices globally and review of studies on Rajaswala paricharya.